Evaluasi Perencanaan Strategis Fakultas Pendidikan Tinggi Islam Berbasis Moderasi Beragama - Rodin, Rhoni; Hamengkubuwono; Warlizasusi, Jumira; Fathurrochman, Irwan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study examines strategic planning in Islamic higher education by analyzing the Strategic Plan (Renstra) of the Faculty of Ushuluddin, Adab, and Da’wah (FUAD) as a case study. Using a descriptive-analytical approach, the study evaluates the alignment of vision, mission, and development strategies with the current challenges of Islamic higher education. The findings show that the strategic plan reflects a progressive vision of religious moderation, but its implementation still faces key challenges, particularly in integrating the vision into teaching, research, and community service, ensuring consistent operational strategies, and strengthening institutional independence. The main contribution of this study lies in highlighting the relationship between strategic planning and the mainstreaming of religious moderation values as a framework for strategic management in Islamic higher education. These findings offer both theoretical insight and policy implications for developing more adaptive, value-based, and sustainable strategic planning in Islamic higher education institutions.